Tackling relationships and species circumscriptions of Octoblepharum, an enigmatic genus of haplolepideous mosses (Dicranidae, Bryophyta). Issue 1 (2nd January 2017) - Santos, Marina Bonfim; Stech, Michael
Abstract : The systematic position of the tropical moss genus Octoblepharum remains under discussion, and in addition, species circumscriptions and relationships of its 18 accepted species remain poorly known. Here we analysed 21 Octoblepharum samples representing four species ( O. albidum, O. arthrocormoides, O. cocuiense, O. pulvinatum ), within a dataset of haplolepideous mosses and markers from all three genomes. Octoblepharum is resolved as monophyletic and sister to the Calymperaceae, and this clade as sister to the Hypodontiaceae. Based on the molecular results and morphological characters, we suggest Octoblepharum to be placed in its own family, the Octoblepharaceae. The analysed Octoblepharum species are molecularly clearly distinguishable. The two included specimens of the rare and little known Asian species O. arthrocormoides were originally labelled as the common and widespread O. albidum, and their recognition may represent the first records of the species after its description. Octoblepharum albidum shows considerable intraspecific molecular variability, which may correspond to morphologically distinguishable groups within a species complex.